Sworn enemies : the divine oath, the book of Ezekiel, and the polemics of exile - Strine, C. A. (Casey Alan), 1975- (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft ;, 2013)
This book explains how Ezekiel uses formulaic language from the exodus origin tradition to craft an identity for the Judahite exiles that refutes an autochthonous origin tradition preferred by the non-exiled Judahites. The book addresses a number of key questions: the relationship between the exodus and patriarchal traditions, Ezekiel's contribution to the development of monotheism, the date and setting of the book of Ezekiel, and Ezekiel's apparent silence about the Babylonians.